(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background : Total Anomalous Pulmonary Venous Return (TAPVR) is a rare congenital cyanotic heart disease. Which typically presents during infancy, late diagnosis in older children is unusual. The clinical manifestation of TAPVR depend on the presence or absence of obstruction of the venous channels. If pulmonary venous return is obstructed, severe pulmonary congestion and pulmonary hypertension develops, presents early with cyanosis and respiratory distress. In contrast, those with mild or no obstruction develops mild to moderate degrees of desaturation following fall in pulmonary vascular resistant. Case Report : We present a case of Total Anomalous Pul- monary Venous Return (TAPVR) with large secundum At- rial Septal Defect (ASD) in a 10 years old boy, presented with mild and nonspecific clinical manifestations might be responsible for the delayed diagnosis. Here is contemporary reminder for taking careful history, focused clinical examination, evaluation by imaging during the assessment of pediatric patients, with prolonged effort intolerance and referral to pediatric cardiologist as required. Conclusion : Most importantly this case illustrates the useful diagnostic value of CT scan of chest as an aid to Echocardiography to evaluate extracardiac vascular morphology. JCMCTA 2020 ; 31 (2) : 152-155